Evaluation of Response of Parenteral Dexamethasone in Pemphigus Vulgaris - Uddin, M Jamal; Maidul, AZMI; Eakub, MA; Wahab, MA; Khondker, L (Community Based Medical Journal, 2013)
A clinical trial was carried out in the Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Dhaka. The total number of patients was thirty and among them fifteen patients were treated with injection dexamethasone (Group-A) and other fifteen were treated with oral prednisolone (Group-B). The study showed that in Group-A, on admission and after 6 weeks, the mean number (±SD) of skin lesion of pemphigus was 36.87±8.40 and 5.27±1.624 respectively. In Group-B, on admission and after 6 weeks, the mean number (±SD) of skin lesion of pemphigus was 36.27±8.980 and 7.73±1.007 respectively. The study also observed that in group-A, on admission and after 6 weeks, the mean number (±SD) of mucous membrane lesion of pemphigus was 3.40±2.633 and 1.00±0.926 respectively. In Group-B, on admission and after 6 weeks, the mean number (±SD) of mucous membrane lesion of pemphigus was 3.33±2.225 and 1.87±1.246 respectively. Statistically significant improvement was observed in both groups in all clinical parameter after 6 weeks. Dexamethasone group showed statistically higher significant improvement than prednisolone group in all clinical parameter except Nikolskys sign. Injection dexamethasone appears to be more effective than oral prednisolone in early management of pemphigus vulgaris. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16694 Community Based Medical Journal 2013 July: Vol.02 No 02: 25-29